Convergence of Radar Cirebon's Journalistic Works from Print Media to Digital Platforms - Alpin Ashary Muzhaffar; Chairul Ardiansyah; Ibnu Hiban Gymnastiar; Farida Nurfalah; Abdul Jalil Hermawan (Athena: Journal of Social, Culture and Society, 2025)
Media convergence is the integration of various platforms in the presentation of information that has become a phenomenon of the journalism industry. This research aims to analyze media convergence in improving the quality of journalistic work and the journalism industry's interpretation of media convergence. With a focus on changes in readers' content consumption habits. This research uses a qualitative approach. This data collection technique uses observation, interviews using purposive sampling techniques, and written document analysis. The unit of analysis of this research involved the general manager and journalists of Radar Cirebon as well as 3 students as news readers. The results showed that Radar Cirebon has implemented media convergence as a response to technological developments and changes in reader consumption patterns that want fast access to news and various formats. However, some aspects of convergence such as information presentation and ad bundling tactics still need to be optimized. The conclusion of this study confirms that although all dimensions of convergence have been implemented, evaluation and training of competent human resources are needed to improve the quality of journalistic works on various platforms of Radar Cirebon